'Made in China 2025': the development of a new energy vehicle industry in China. Issue 1 (2nd January 2019) - Yeung, Godfrey
ABSTRACT: This paper examines how the state can facilitate the establishment of a domestic production network in new energy vehicles (NEVs), from the making of electric vehicle batteries and battery management systems to the manufacturing of NEVs. The case of China illustrates how a non-firm actor was able to create the largest NEV market in the world by implementing proactive policies for market creation and new industrial regulations for cost and range parity. To facilitate the further development of domestic production networks for NEVs, the Chinese government shifted its regulatory parameters and leveraged the market size to drive the incumbent global automakers to rejig their product portfolios and form joint ventures with domestic NEV-makers in China. This provides a prima facie case illustrating how a proactive state can take a dominant role in establishing a domestic production network without coupling with global lead firms in global production networks.